Impact of burosumab on lower limb alignment in children with X-linked hypophosphatemia - David B. Frumberg, MD, FAAOS; J. Lawrence Merritt, II, MD; Angel Chen, MSc; Thomas O. Carpenter, MD (Elsevier, 2024)
ABSTRACT: Background: Osteotomy and hemiepiphysiodesis are used to treat lower limb deformities in the rare musculoskeletal disease X-linked hypophosphatemia (XLH), but postsurgical complications and malalignment recurrence are possible. This retrospective analysis assessed whether treatment with burosumab, a fully human IgG1 monoclonal antibody to fibroblast growth factor 23 approved for treatment of rickets in XLH, improves lower limb malalignment toward age-specific normal values in children with XLH. Methods: Children with confirmed XLH received burosumab for 160 weeks in the open-label phase 2 study CL205, or conventional therapy (Pi/D) or burosumab for 64 weeks in the randomized, open-label phase 3 study CL301, with crossover from Pi/D to burosumab through 88 weeks. Full-length, anteroposterior lower limb radiographs were reviewed. The mechanical femoral-tibial angle (MFTA) of lower limbs was measured at baseline and postbaseline. Each MFTA was classified as normal (within 1 standard deviation [SD] of age-specific normal range) or clinically normal (within 2 degrees of normal). Results: Overall, 116 limbs were included (CL205, n = 26; CL301, n = 90). Varus or valgus limbs were observed at baseline in 21 (80.8%) limbs in CL205 and in 69 (76.7%) limbs in CL301. In CL205, mean (SD) MFTA decreased from 13.0° (6.7°) at baseline to 5.7° (6.0°) at week 64 and 1.0° (4.8°) at week 160. In CL301, mean (SD) MFTA decreased from 15.5° (13.6°) at baseline to 8.5° (10.0°) at week 64 in the burosumab arm, and in the crossover arm, from 9.2° (10.4°) at week 64 to 6.9° (9.4°) at week 88 (after 22 weeks of burosumab). The proportion of normal or clinically normal limbs increased with burosumab in CL205 (baseline to week 160, 19.2% to 58.3%) and in the CL301 burosumab arm (baseline to week 64, 19.6% to 37.0%) but not in the CL301 crossover arm (week 64-88, 34.1% to 33.3%). Conclusions: In children with XLH, long-term treatment with burosumab is capable of correcting the MFTA of varus and valgus lower limbs to a neutral alignment without requiring surgical intervention. Key Concepts: 1. Treatment with burosumab led to the correction of lower limb angular deformity to neutral alignment in children with X-linked hypophosphatemia (XLH). 2. Continued treatment with burosumab for at least 1 year appears to have further positive effects on the correction of lower limb angular deformity in children with XLH. 3. Initial treatment with burosumab is indicated in young children with XLH for whom hemiepiphysiodesis is being considered. Level of Evidence: III